(untitled) - Powell, Lynn (New York, 2005)
This rigorous tutorial is aimed at both power system professionals and electrical engineering students. Breaking down the complexities of load flow analysis into a series of short, focused chapters, the book develops each of the major algorithms used, covers the handling of generators and transformers in the analysis process, and details how these algorithms can be deployed in powerful software. Having read the book, and EE student or engineer will have all the tools necessary to predict load usage and prevent overloads, blackouts, and brownouts.
Keywords: Electric power systems; Load dispatching